Customer relationship management model for Alumni Liaison Unit (UTM) - Ahmadi, Hossein (2012)
In today’s competitive marketplace, educational institutions are sellers proposing courses, a degree, and a rich alumni life. It is more helpful for universities to keep its graduate students as alumni than recruit new students and new supporters for the university to decrease substantially amount of cost. Students are purchasers who register for courses, apply for graduation, and make donations as alumni. The longer these ongoing transactions are satisfactory to both parties, the longer the relationship will endure, to the benefit of every one. In this regard, one extremely useful technique to improve this relationship which has been adopted by many corporations is Customer Relationship Management (CRM). The aim of this research is to provide a better understanding of the usage of CRM based IDIC process model for Alumni Liaison Unit to improve relationship between UTM and its alumni community. Basically, this thesis conducted two research approaches; the first one is qualitative method on the basis of analysis of the empirical data gathered from structured personal interview across Alumni Liaison Unit as research case study. The second research method is quantitative method on the basis of analysis of the statistical data gathered from the distributed questionnaire to customers (graduate students). In fact, both research approaches were accompanied with intense support of literature review which has lead to the creation of new CRM strategy model. The role of this CRM model is to aid organization to realize a one-to-one relationship with customers and customize product and services to offer according to their values and needs.